Implementasi Bimbingan Pribadi-sosial pada Siswa di SDK Pahar Kecamatan Lelak Kabupaten Manggarai - Bosco, Fabianus Hadiman (JIPD (Jurnal Inovasi Pendidikan Dasar), 2019)
This research is based on the social problem of the students in SDK Pahar. The social problem of the student is rooted from an individual or certain individual which has effect to other people. The social problem of the student which occur are the students are not afraid to say bad words and ridicule to other students in front of the students, cutting the class, and leaving the class during the classroom interaction. This research is aiming to know how far the applying of the individual guidance which  run in SDK Pahar , the region of Lelak in Manggaraim regency. The strategy which applied in individual-social guidance, the kind of guidances, and the hindrances of applying is being focused of this research.              The method of this research is qualitative method. The data gathering through interview. The data validity is the tringulasy method. The data analisys through data reduction, data display and data conclusion. The subject of this research is the headmaster and the teachers in SDK Pahar. The result of this research, fisrt, the strategy which is used is personal guidance, group guidance, the collaboration between teacher guidance, the cooperate between teachers and the student’s parent. Second, the guidance individual-social is happening accidentally. Third, the hindrance of individual-social guidance in terms of time, program, room and professional assistace which make the guidance is not maximum.